2013
DOI: 10.1038/ejhg.2013.193
|View full text |Cite
|
Sign up to set email alerts
|

The FMR1 CGG repeat test is not a candidate prescreening tool for identifying women with a high probability of being carriers of BRCA mutations

Abstract: The identification of women with a high probability of being carriers of pathogenic BRCA mutation is not straightforward and a major improvement would be the availability of markers of mutations that could be directly evaluated in individuals asking for genetic testing. The FMR1 gene testing was recently proposed as a candidate prescreening tool because an association between BRCA pathogenic mutations and FMR1 genotypes with 'low alleles' (CGG repeat number o26) was observed. To confirm this hypothesis, we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 10 publications
1
10
2
Order By: Relevance
“…We, however, were unable to detect any difference in distribution of low FMR1 alleles in comparison to reported distributions in normal infertile populations without known malignancies [1], [12][14], nor were we able to demonstrate a relative increase in low FMR1 alleles in BRCA1 /2 carriers with ovarian cancers in comparison to ovarian cancer patients who were not BRCA1 /2 mutation carriers.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…We, however, were unable to detect any difference in distribution of low FMR1 alleles in comparison to reported distributions in normal infertile populations without known malignancies [1], [12][14], nor were we able to demonstrate a relative increase in low FMR1 alleles in BRCA1 /2 carriers with ovarian cancers in comparison to ovarian cancer patients who were not BRCA1 /2 mutation carriers.…”
Section: Discussioncontrasting
confidence: 94%
“…In contrast, even excluding the 78.8% prevalence of low FMR1 alleles in the Austrian study (likely even underreported since rare hom patients were not sub-divided in that study, thus not including hom-high/low and hom-low/low patients), the Dutch [12] reported 35.0% prevalence and the Italians [14] a 32.6% prevalence of low FMR1 alleles. Only the Israeli study [13], therefore, like here reported ovarian cancer data, reported an actually inverted picture of more low FMR1 alleles in BRCA1 /2-negative than BRCA1 /2-positive women.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Lately, Brandao et al 16 and Ricci et al 17 have independently shown that the distribution of the FMR1 subgenotypes in BRCA mutation carriers compares well with that obtained from non carriers, concluding that BRCA1/2 mutations are not associated with FMR1 low subgenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Gleicher and coworkers presented ovarian cancer patients with BRCA1/2 mutations had no relative increased low FMR1 alleles compared to the patients without BRCA1/2 mutations (Gleicher et al 2014). Ricci et al (2014) also illustrated FMR1 genetic testing was inappropriate to prescreen the related BRCA mutations. Dagan et al (2014) strengthened the evidence by the parallel epidemiological studies.…”
Section: Low Numbers Of Cgg Repeatmentioning
confidence: 99%